PENGARUH VARIASI METODE PEMBELAJARAN PADA PRESTASI BELAJAR SISWA MATA PELAJARAN KIMIA - Lia Herlina; Eny Winaryati (Universitas Muhammadiyah Semarang, 2017)
Student learning result are everything from the learning result that have been followed by students in the form of values and attitudes that have fulfilled the minimal mastery. Good achievement is influenced by good learning process also, the method used by the teacher is one of them. The purpose of this research is to determine whether or not the influence of the methods that teachers use in the achievement of SMAN 9 Semarang especially chemistry subjects. The method used in this research is descriptive research type with quantitative approach. Quantitative descriptive research is data obtained from the sample population studied in accordance with statistical methods used, with data collection techniques there are three kinds, such as questionnaires, interviews, and observation. The result of this research is the method of learning affect student achievement with the value of 2.88 and including the high category, it is confirmed by the results of interviews and observation that the varied learning methods will attract students' attention in learning and generate maximum achievement. Keywords: learning method, learning performence.